Balloon angiopLasty for intracranial Atherosclerotic minor Stroke/TIA (BLAST): study protocol for a multicenter prospective cohort study - Qi, Shuang; Liu, Liang; Yue, Fei-Xue; Qiu, Jing; Li, Wei; Li, Chao; Nguyen, Thanh N.; Wei, Ming; Chen, Hui-Sheng; Wang, Shou-Chun (Frontiers in Neurology, 2024)
Rationale/Aim Intracranial atherosclerotic stenosis (ICAS) is a common cause of stroke in Asia and is significantly associated with stroke recurrence. The Balloon angiopLasty for intracranial Atherosclerotic minor Stroke/TIA (BLAST) study aims to evaluate the safety and effectiveness of early submaximal balloon angioplasty (SBA) combined with standard medical therapy vs. standard medical therapy alone in patients with minor stroke or transient ischemic attack (TIA) due to ICAS. Methods The BLAST study is a multicenter prospective cohort study which will enroll patients with minor stroke or TIA due to symptomatic ICAS within 1 week of symptom onset from 20 centers in China. Eligible patients will receive either SBA with standard medical therapy or standard medical therapy alone based on the decision of the patient or legal representative. Participants will be followed up for 1 year. Study outcomes The primary outcome is a composite of stroke or death within 30 days or ischemic stroke in the culprit artery territory from 30 days to 1 year. Secondary outcomes include stroke or death within 30 days, ischemic stroke in the culprit artery territory from 30 days to 1 year, restenosis rate of the culprit artery at 1 year, and neurological improvement at 90 days (assessed by mRS score). Safety outcomes include intracranial hemorrhage within 30 days and endovascular complications. Sample size estimate According to previous studies, the incidence of the composite clinical outcomes is 15% in the group receiving medical therapy alone. We assumed the incidence would decrease to 5% in the SBA combined with the medical therapy group. The target sample size is 416 patients (208 per group), with 90% power and 5% type I error, allowing for a 10% loss to follow-up. Implications The BLAST study will provide evidence regarding whether early SBA can reduce stroke recurrence and mortality in patients with minor stroke/TIA due to ICAS compared with medical therapy alone. Clinical trial registration:Clinicaltrials.gov, NCT06014723.